Pengaruh Konflik Pekerjaan-Keluarga dan Konflik Keluarga-Pekerjaan pada Stres Kerja: Studi pada Karyawan Fakultas Ekonomika dan Bisnis UGM - , ANGGRAENI PRANANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Work-family conflict has two direction, namely work-family conflict and family-work conflict. Work-family conflict occurs when work interfering family life. Whereas, familywork conflict occurs when family interfering work life. Based on the two-way-relationship, it can be indicated that work-family conflict and family-work conflict is a predictor of job stress. This research analyzed the effect of work-family conflict and family-work conflict to job stress, the objects are employee of Economics and Business Faculty Universitas Gadjah Mada. This research was carried out by processing the primary data collected by quetionnaire. There are two hypotheses in this research were tested by multiple liner regression. The result of this research stated that the Work-Family Conflit (WFC) and the Family-Work Conflict (FWC) has a significant positive effect on Job Stress to employees who are married and have children. The higher of work-family conflict, the higher the level of job stress. Keywords: Work-Family Conflict, Family-Work Conflict, Job Stress, Stress, Conflict